Screening for the Risk Level of Cardiovascular Disease in the Community in Nagari Sungai Buluh Selatan - Emil Huriani; Fitri Mailani; Mulyanti Roberto Muliantino; Rahmi Muthia; Tiurmaida Simandalahi; Dally Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Cardiovascular diseases are diseases that cause high mortality and morbidity that can be prevented or reduced in risk of occurrence. However, there are still many people who do not make efforts to determine the level of risk of cardiovascular disease and do not know the efforts needed to reduce their risk of cardiovascular disease. This community service activity aimed to carry out health examination, identify risk factors and determine the risk of cardiovascular diseases in the community in Nagari Sungai Buluh Selatan, Batang Anai District, Padang Pariaman Regency, West Sumatra. Activities are carried out using physical examination, assessing the level of disease risk and individual education about reducing the risk of cardiovascular disease methods. The instrument used to determine the level of risk is the Jakarta Cardiovascular Score. The results of this activity showed that 44.8% of the population had a moderate risk of suffering from cardiovascular diseases. It is hoped that community health centres will carry out risk level screening and education on reducing the risk of cardiovascular diseases as routine and structured activities in order to increase public awareness in preventing and reducing the risk of cardiovascular diseases.